Kinetics thermodynamics and adsorption study of raw treated diatomite as a sustainable adsorbent for crystal violet dye - Mokhtar Saidi; Bendoukha Abdelkrim Reguig; Mohammed El Amine Monir; Talal M. Althagafi; M. Fatmi; Abderahmane Remil; Abdelhafid Zehhaf; M. A. Ghebouli (Scientific Reports)
Abstract Adsorption is a simple and effective method to remove heavy metal ions and anionic or cationic dyes from aqueous or waste solutions. Herein, we report on the adsorption of a cationic dye crystal violet on a low-cost natural material. The diatomite was obtained from Sig deposit (west of Algeria) and then treated with 1 M HCl solution. Natural clay (diatomite) was characterized using different physical-chemical methods, including, X-ray powder diffraction, X-ray fluorescence, thermogravimetric analysis, scanning electron microscopy, and Fourier transform infrared and pH of zero charge. The effect of various experimental parameters, such as initial dye concentration, adsorbent dose, initial pH, and shaking time on adsorption was investigated. The maximum adsorption capacity was found to be 82.0 mg.g− 1 for treated Diatomite and 75.0 mg.g− 1 for raw diatomite, with equilibrium reached within 120 min. Adsorption kinetics followed the pseudo-second-order model, with high correlation coefficients (R² = 0.998 for treated diatomite and R² = 0.999 for raw diatomite). The isotherm data showed the best fit with the Langmuir model. Optimal adsorption occurred at pH 8 for treated diatomite and pH 10 for raw diatomite.